Japanese encephalitis in north-east, India: Pharmacotherapeutic perspectives - Moksood Ahmed Laskar; Priyam Jyoti Das; Mrinmoy Basak; Juganta Kumar Kalita; Santa Mandal (The Microbe)
Japanese Encephalitis (JE) poses a significant health threat in North-East India, with seasonal outbreaks causing substantial morbidity and mortality. Studies report an incidence rate of approximately 4.4 cases per 100,000 population annually. The disease's neuroinvasive nature leads to severe neurological complications, with mortality rates ranging from 20 % to 30 %. Understanding JE's epidemiology is crucial; for instance, a study found that 85 % of cases occurred in rural areas. JE targets neurons in the central nervous system, resulting in neuronal death and inflammation. Management involves supportive care, with antiviral drugs like ribavirin showing promise in reducing mortality. Vaccination remains the cornerstone of prevention, with the live attenuated JE vaccine demonstrating over 90 % efficacy. However, challenges such as vaccine coverage gaps persist, emphasizing the need for improved surveillance and vaccine accessibility to mitigate JE's impact in North-East India. This study provides insights into the epidemiology, pathophysiology, and management perspectives of JE in the region, highlighting the importance of integrated approaches to combat this public health threat.